Role of Organizational Psychology in Human Resource Management - Daniil Riumin (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Virtual Conference, 10-12 September 2020, 2020)
Started at the end of 19th century as a branch of classical psychology showing an interest in human mind and behaviour, Organizational Psychology rapidly grew to the independent field of research nowadays and continue to grow connecting many spheres of organizational studies. Human Resource Management the closest and the closest sphere that is using as a help achievement of Organizational Psychology – its theories and methods in work as soon as in both personality is the object of work and research. The purpose of this paper is to understand in more details what is the Organizational Psychology, what is its goals, how is it connected to Human Resource Management, and how Organizational Psychology supports Human Resource Management in its everyday work.
Keywords: M54; 330; human resource management; organizational psychology; industrial psychology